Nutritional status, biological maturation and cardiorespiratory fitness in Azorean youth aged 11-15 years - Coelho-e-Silva, Manuel J.; Vaz Ronque, Enio R; Cyrino, Edilson S; Fernandes, Rômulo A. [UNESP]; Valente-Dos-Santos, João; Machado-Rodrigues, Aristides; Martins, Raul; Figueiredo, António J; Santos, Rute; Malina, Robert M (Springer Nature, 2013)
Background: Sex and individual differences in biological maturity status can influence height, weight, and body fat. Thus, the rigorous control of these variables seems necessary for estimating overweight and obesity in adolescents. The aims of this study were to estimate the prevalence of overweight and obesity and over-fatness in Azorean adolescents and to examine the contributions of chronological age, sex, estimated maturity status, and cardiorespiratory fitness (CRF) to the risk of overweight and obesity and over-fatness. Methods. The sample comprised 1,206 youth aged 11-15 years (626 boys and 580 girls) from the Azores Islands, Portugal. Body mass, stature, and skinfolds (triceps and subscapular) were measured. Body mass index (BMI) was calculated and percent fat was predicted from skinfolds. Age- and sex-specific IOTF cut-off values of the BMI defined nutritional status. Biological maturation was estimated as present height expressed as a percentage of predicted adult (mature) stature. The CRF was analyzed from the 20-m shuttle run test. Results: The total prevalence rates of overweight/obesity and over-fatness were of 31% and 27%, respectively. Low CRF (unfit) and being average and advanced in maturity status were positively and significantly associated with overweight/obesity and with risk of being over-fatness in both sexes. Conclusions: High prevalence rates of overweight/obesity and over-fatness were identified in Azorean youth, and low CRF and advanced biological maturation were positively associated with overweight/obesity and over-fatness in our sample of adolescents. © 2013 Coelho-e-Silva et al.; licensee BioMed Central Ltd.
Keywords: adolescent; age; Atlantic islands; body mass; body weight; cardiovascular system; child; exercise test; female; fitness; human; male; nutritional status; obesity; respiratory system; sexual maturation; Adolescent; Age Factors; Azores; Body Mass Index; Cardiovascular System; Child; Exercise Test; Female; Humans; Male; Nutritional Status; Overweight; Physical Fitness; Respiratory System; Sexual Maturation; Thinness